A Scenario for Publishing Mathematics in the Future - Rob Kirby (Issues in Science and Technology Librarianship, 1998)
I offer a (not original) scenario, suitable for mathematics, for electronic distribution of e-prints followed by journal submission (with its refereeing, editing and acceptance/rejection) and publication in low cost paper journals for the higher quality papers.